PROMOTION OF DENTAL AND ORAL HEALTH THROUGH THE GIGIKU SEHAT APPLICATION AND HEALTHY DENTAL GYMNASTICS WITH TEACHER ASSISTANCE ON TEETH CLEANING ACTIONS TO PREVENT CARIES IN CHILDREN AGED 10-13 YEARS - Muhammad Nurung1, Andi Zulkifli2, Sudirman Nasir3, Wahiduddin4, Santi Martini5, Harun Achmad6, Anwar Mallongi7, Fridawaty Rivai8 (Chelonian Research Foundation, 2024)
BACKGROUND: Caries is one of the chronic diseases experienced by 2.4 billion or 36% of the world's population. Globally, school children who experience caries account for 60%-90% due to lack of health promotion. Mobile mobile is one of the health promotions that can improve the degree of public health. AIM: Knowing the effect of the application of healthy teeth and healthy dental gymnastics with teacher assistance on the act of cleaning teeth to prevent caries in children aged 10-13 years. METHOD: The study was conducted at Makassar City Elementary School, South Sulawesi in September 2022 - March 2023. The type of research is a mixed method with two stages of research, stage 1 making healthy dental applications with qualitative methods and stage 2 educational model intervention for 3 (three) months with quasi-experimental methods with the design of the non randomized pretest postest control group design. The number of samples were students of SD Hang Tuah 64 people, SDN Ujung Tanah 54 people and SDN Cambaya 49 people. The research group was divided into 3 (three) with teacher assistance, namely First is SD Hang Tuah with a combination intervention of healthy dental application and healthy dental gymnastics. The second is SDN Ujung Tanah with the intervention of my healthy teeth application. The third is SDN Cambaya with healthy dental gymnastics intervention. RESULTS: The level of oral hygiene at SD Hang Tuah was significantly different before and after the intervention, while at SDN Ujung Tanah and SDN Cambaya there was no significant difference but there was a difference in mean value. The DMFT scores in the three schools have significant differences, especially the mean value in the Filling aspect has increased which is an indicator of increased awareness to treat caries. CONCLUSION: The effect of dental health education with the application of healthy teeth and / or healthy dental gymnastics with teacher assistance statistically had a significant effect on SD Hang Tuah, while SDN Ujung Tanah and SDN Cambaya did not have a significant effect but there was a difference in mean values on improving oral hygiene. The DMFT value before and after the intervention statistically has a significant effect, especially in the Filling aspect, there is an increase in the mean value which is an indicator of increased awareness to treat caries. Keywords: Caries, oral health promotion, oral health behavior